Detection Of Formaldehyde In White Tofu At A Tofu Factory Ujung Batu Sub-District, Rokan Hulu Regency - Wahyudi, Tino; Al Muzafri; Yuliana Susanti (Universitas Pasir Pengaraian, 2025)
Synthetic preservatives are dangerous preservatives that are prohibited for food and are declared hazardous ingredients according to the regulation of the Minister of Health (Menkes) Number. 1168/Menkes/Per/X/1999. One of the dangerous compounds that is often used is formalin. The use of formalin is rife among white tofu sellers, because formalin is considered the most effective for preserving white tofu. The purpose of this study was to determine the presence or absence of formalin content in white tofu produced by the Ujung Batu District Factory, Rokan Hulu Regency. Based on the examination of formalin tests on 7 white tofu samples that were sampled and analyzed, it showed that 3 white tofu samples at the Ujung Batu District Factory were identified as containing formalin, namely A, E and F. The samples tested showed purple final results which indicated positive if the sample turned purple. While 4 samples of white tofu, do not contain formalin, namely B, C, D and G. The tested sample showed the final result did not change color, which indicates negative. The organoleptic test assessment of both texture, aroma and color has conformity with the results of the formalin kits test conducted in the laboratory. White tofu that positively contains formalin has a very chewy texture, pungent aroma and slightly white color.